Foot Assessment Clinical Scales in Charcot-Marie-Tooth Patients: A Scoping Review - Rambelli, Chiara; Mazzoli, Davide; Galletti, Martina; Basini, Giacomo; Zerbinati, Paolo; Prati, Paolo; Mascioli, Francesca; Masiero, Stefano; Merlo, Andrea (Frontiers in Human Neuroscience, 2022)
Introduction Charcot-Marie-Tooth disease (CMT) is a slow and progressive peripheral motor sensory neuropathy frequently associated with the cavo-varus foot deformity. We conducted a scoping review on the clinical scales used to assess foot deviations in CMT patients and analyzed their metric properties. Evidence Acquisition A first search was conducted to retrieve all scales used to assess foot characteristics in CMT patients from the Medline, Web of Science, Google Scholar, Cochrane, and PEDro databases. A second search was conducted to include all studies that evaluated the metric properties of such identified scales from the same databases. We followed the methodologic guidelines specific for scoping reviews and used the PICO framework to set the eligibility criteria. Two independent investigators screened all papers. Evidence Synthesis The first search found 724 papers. Of these, 41 were included, using six different scales: “Foot Posture Index” (FPI), “Foot Function Index”, “Maryland Foot Score”, “American Orthopedic Foot & Ankle Society's Hindfoot Evaluation Scale”, “Foot Health Status Questionnaire”, Wicart-Seringe grade. The second search produced 259 papers. Of these, 49 regarding the metric properties of these scales were included. We presented and analyzed the properties of all identified scales in terms of developmental history, clinical characteristics (domains, items, scores), metric characteristics (uni-dimensionality, inter- and intra-rater reliability, concurrent validity, responsiveness), and operational characteristics (normative values, manual availability, learning time and assessors' characteristics). Conclusions Our results suggested the adoption of the six-item version of the FPI scale (FPI-6) for foot assessment in the CMT population, with scoring provided by Rasch Analysis. This scale has demonstrated high applicability in different cohorts after a short training period for clinicians, along with good psychometric properties. FPI-6 can help health professionals to assess foot deformity in CMT patients over the years.